Qualitative and Quantitative Analysis of Phenolic Compounds in Spray-Dried Olive Mill Wastewater - Benincasa, Cinzia; Pellegrino, Massimiliano; Romano, Elvira; Claps, Salvatore; Fallara, Carmelo; Perri, Enzo (Frontiers in Nutrition, 2022)
Three-phase olive oil extraction process requires the addition of large amount of water to the system which is difficult to dispose for its load of toxic pollutants. In the other hand, olive mill wastewater is a rich source of bioactive substances with various biological properties that can be used as ingredients in the food industry for obtaining functional and nutraceutical foods as well as in the pharmaceutical industry. In this work, we present the results relative to the phenolic compounds detected in dried olive mill wastewaters. The drying process was achieved by means of spray dryer. Qualitative and quantitative analyses were obtained by liquid chromatography tandem mass spectrometry. In particular, the compounds here discussed are: apigenin (9,55 mg/kg), caffeic acid (2,89 mg/kg), catecol (6,12 mg/kg), p-cumaric acid (5,01 mg/kg), diosmetin (3,58 mg/kg), hydroxytyrosol (1481 mg/kg), hydroxytyrosyl oleate (564 mg/Kg), luteolin (62,38 mg/kg), luteolin-7-O-glucoside (88,55 mg/kg), luteolin-4-O-glucoside (11,48 mg/kg), oleuropein (103 mg/kg), rutin (48,52 mg/kg), tyrosol (2043 mg/kg), vanillin (27,70 mg/kg) and verbascoside (700 mg/kg).